Q Is for Quarry - Sue Grafton (New York Berkley Books, 2003)
Eighteen years after the body of an unidentified young woman is discovered in a quarry off California's Highway 1, two police detectives nearing retirement enlist Kinsey Millhone's aid to help identify the long-ago murder victim
Keywords: Literature (3GdCOHs; General -- Fiction; Millhone, Kinsey (Fictitious character); Women private investigators -- California -- Fiction